Recent development of polymer nanomicelles in the treatment of eye diseases - Cai, Ruijun; Zhang, Ling; Chi, Hao (Frontiers in Bioengineering and Biotechnology, 2023)
The eye, being one of the most intricate organs in the human body, hosts numerous anatomical barriers and clearance mechanisms. This highlights the importance of devising a secure and efficacious ocular medication delivery system. Over the past several decades, advancements have been made in the development of a nano-delivery platform based on polymeric micelles. These advancements encompass diverse innovations such as poloxamer, chitosan, hydrogel-encapsulated micelles, and contact lenses embedded with micelles. Such technological evolutions allow for sustained medication retention and facilitate enhanced permeation within the eye, thereby standing as the avant-garde in ocular medication technology. This review provides a comprehensive consolidation of ocular medications predicated on polymer nanomicelles from 2014 to 2023. Additionally, it explores the challenges they pose in clinical applications, a discussion intended to aid the design of future clinical research concerning ocular medication delivery formulations.